A case and literature review of axial spondyloarthritis and immunoglobulin A vasculitis: Rare association or under-recognized? - Robin Sia; Mueed Mian (SAGE Open Medical Case Reports)
Axial spondyloarthritis (axSpA) is a chronic inflammatory arthritis affecting the spine and sacroiliac joints, often accompanied by extra-musculoskeletal manifestations involving the eyes, gut, and skin. Other organ systems, including the heart (aortic insufficiency), lungs (upper-lobe predominant interstitial fibrosis), and kidneys (nephritic syndrome), may also be affected. Immunoglobulin A vasculitis (IgAV), formerly known as Henoch–Schönlein purpura, is the most common systemic vasculitis in children and is typically self-limited. It is characterized by palpable purpura, arthritis or arthralgia, abdominal pain, and renal involvement. Studies suggest a potential link between elevated serum immunoglobulin A levels and active inflammation in axial spondyloarthritis. Here, we present a case of a Caucasian male diagnosed with immunoglobulin A vasculitis, leading to the identification of previously unrecognized axial spondyloarthritis. In addition, we reviewed the current literature on IgAV occurring in patients with axial spondyloarthritis.